A Systematic Analysis of the Literature on the Post-Covid-19 Condition in Latin America Focusing on Epidemiology, Clinical Characteristics, and Risk of Bias; [Un Análisis Sistemático de la Literatura Sobre la Condición Post-Covid-19 en América Latina Centrado en la Epidemiología, Las Características Clínicas y el Riesgo de Sesgo] - Bachelet-Norelli, V; Silva-Ayarza, I (Medwave Estudios Ltda, 2025)
This analysis article aimed to identify and analyze all articles published on the post-COVID-19 condition in Latin America and the Caribbean, focusing on epidemiology, clinical characteristics, and risk of bias. We did a systematic survey of the literature with broad inclusion criteria. The only exclusion criteria were articles referring to post-acute COVID-19 sequelae after an intensive care unit stay, which we distinguish from the post-COVID-19 condition. We searched MEDLINE/PubMed, LILACS, SciELO, Scopus, Web of Science, and Epistemonikos. We included 55 records, of which 48 were original articles (44 were observational research, 29 of which had a comparison group; and four reviews). Various definitions for long COVID were reported, or none, and few used the World Health Organization criteria. None of the included studies reported prevalence rates for the region. We extracted the reported signs and symptoms of long COVID for our region. Using the Johanna Briggs Institute critical appraisal tools for observational analytic research, we found that most included studies were prone to limitations and biases. We conclude that more research should be done on the post-COVID-19 condition in Latin America and the Caribbean, using rigorous study designs to inform public health strategies. © 2025, Medwave Estudios Ltda. All rights reserved.